THE USE OF FLOTATION METHOD FOR PURIFICATION OF WASTEWATERS CONTAMINATED WITH OIL PRODUCTS - Maksymiuk, Mariia; Kravchuk, Tetiana; Titova, Olha; Kosenko, Olena; Spaska, Olena (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
Industrial and natural wastewater is one of the factors of environmental pollution, in particular, its water basin. Among others, fuel and oil pollutants are toxic substances that cause significant harm to all living things. It is necessary to create technologies using effective methods of wastewater treatment to solve such problems. It is possible to properly select and effectively use methods of treatment taking into account the nature, condition and concentration of contaminants in wastewater. These are the issues addressed in this article. Particular attention is paid to the use of flotation as a method of purification of stable highly dispersed emulsified wastewater containing oil or fuel contaminants in the technology of this type wastewater treatment. The main objectives of the study were to evaluate the impact of parameters and flotation reagents on the efficiency of the process of purification of stable highly dispersed emulsified wastewater. Flotation of these wastewaters was carried out on a laboratory flotation installation of pneumatic type and compared with the process of wastewater settling over time. Studies have shown that for stable emulsified wastewater containing oil or fuel contaminants with a low content of highly dispersed particles of inorganic nature or a stabilizer is present in them, it is advisable to use the flotation method with flotation units of pneumatic type. Analysing the results, it should be noted that the flotation method significantly reduces the purification time of highly dispersed emulsified wastewater from 3-5 hours of their settling in settling tanks-oil traps up to 10-20 minutes by the method of pneumatic flotation, while the degree of wastewater treatment increases in at least 1.5 - 2 times depending on the presence of fuel or oil contaminants in wastewater. If the wastewater contains a stabilizer, such as a surfactant, it can be used as an effective flotation reagent in the purification of this type of wastewater by flotation, which is not suitable for the settling process.